Investigation of variation in temperature on steep subthreshold slope nanowire tunnel field effect transistor based biosensor. (1st September 2022) - Sachdeva, Rohit; Bhushan, Aditya; Bajaj, Aayush; Gupta, Maneesha; Kumar, Prateek; Raman, Ashish; Ranjan, Ravi; Kumar, Naveen
Abstract: Biosensors are critical part of today's lifestyle. They have vast applications in medical industries making continuous advancement in the domain crucial. To further extend their utilities in this manuscript effect of variation in temperature on charge plasma based tunnel field effect transistor as biosensor is investigated. To investigate, device is simulated at 200 K, 300 K and 400 K and various device, analog and linearity characteristics are examined. To create the cavity for accommodation of biomolecules, source electrode is extended. Analyzed device resulted in steepest subthreshold slope of 17.61mV dec −1 and 8.81mV dec −1 for κ = 3 at T = 200 K. Device also has high ION sensitivity for entire temperature range. Due to promising characteristics, investigated biosensor can be used in future for detection of different biomolecules.